Acute high altitude exposure, acclimatization and re-exposure on nocturnal breathing - Furian, Michael; Bitos, Konstantinos; Hartmann, Sara E.; Muralt, Lara; Lichtblau, Mona; Bader, Patrick R.; Rawling, Jean M.; Ulrich, Silvia; Poulin, Marc J.; Bloch, Konrad E. (Frontiers in Physiology, 2022)
Background Effects of prolonged and repeated high-altitude exposure on oxygenation and control of breathing remain uncertain. We hypothesized that prolonged and repeated high-altitude exposure will improve altitude-induced deoxygenation and breathing instability. Methods 21 healthy lowlanders, aged 18-30y, underwent two 7-day sojourns at a high-altitude station in Chile (4-8hrs/day at 5050m, nights at 2900m), separated by a 1-week recovery period at 520m. Respiratory sleep studies recording mean nocturnal pulse oximetry (SpO2), oxygen desaturation index (ODI, >3% dips), breathing patterns and subjective sleep quality by visual analog scale (SQ-VAS, 0-100% with increasing quality), were evaluated at 520m and during nights 1 and 6 at 2900m in the 1st and 2nd altitude sojourn. Results At 520m, mean±SD nocturnal SpO2 was 94±1%, ODI 2.2±1.2/h, SQ-VAS 59±20%. Corresponding values at 2900m, 1st sojourn, night 1 were: SpO2 86±2%, ODI 23.4±22.8/h, SQ-VAS 39±23%; 1st sojourn, night 6: SpO2 90±1%, ODI 7.3±4.4/h, SQ-VAS 55±20% (P<0.05, all differences within corresponding variables). Mean differences (, 95%CI) in acute effects (2900m, night 1, vs. 520m) between 2nd vs. 1st altitude sojourn were: SpO2 0%(-1 to 1), ODI -9.2/h(-18.0 to -0.5), SQ-VAS 10%(-6 to 27); differences in acclimatization (changes night 6 vs.1), between 2nd vs. 1st sojourn at 2900m were: SpO2 -1%(-2 to 0), ODI 11.1/h(2.5 to 19.7), SQ-VAS -15%(-31 to 1). Conclusion Acute high-altitude exposure induced nocturnal hypoxemia, cyclic deoxygenations and impaired sleep quality. Acclimatization mitigated these effects. After recovery at 520m, repeated exposure diminished high-altitude-induced deoxygenation and breathing instability, suggesting some retention of acclimatization while subjective sleep quality remained similarly impaired. Clinical Trial Registration clinicaltrials.gov NCT02730143